2013
DOI: 10.1590/s1983-40632013000200014
|View full text |Cite
|
Sign up to set email alerts
|

Calendário agrícola para a cultura do milho em Sinop (MT)

Abstract: A região Centro-Oeste ocupa a segunda posição no cenário nacional, em produção de milho, tendo o Estado de Mato Grosso como principal produtor, com, aproximadamente, 46% da produção e mais de 1.650.000 hectares plantados (Conab 2010). Para se obter um bom rendimento na atividade agrícola, é necessário que haja uma interação importante entre as condições do meio ambiente e a cultura, desde antes do plantio até a pós-colheita, sendo a precipitação pluvial e a temperatura do ar, juntamente com o fotoperíodo, as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The Central-West region, for example, ranks first nationally in corn and soybean production, with the State of Mato Grosso as the main producer of both crops, producing approximately 64% of maize and 60% of soybeans, with more than 4,498,000 and 9,518,000 hectares planted, respectively (CONAB, 2019). According to Garcia et al (2013), in a study carried out in the Sinop region (MT), the best growing season indicated for maize crop corresponds to the wet season during spring and summer, which favors high water availability to the soil due to rainfall and less probability of occurrence of consecutive dry days. The authors also affirm that in order to obtain a good income from the agricultural activity, it is important to know the conditions of the environment and the culture, from before planting until postharvest, as the rainfall and the temperature of the air, together with the photoperiod, are the main meteorological variables for productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The Central-West region, for example, ranks first nationally in corn and soybean production, with the State of Mato Grosso as the main producer of both crops, producing approximately 64% of maize and 60% of soybeans, with more than 4,498,000 and 9,518,000 hectares planted, respectively (CONAB, 2019). According to Garcia et al (2013), in a study carried out in the Sinop region (MT), the best growing season indicated for maize crop corresponds to the wet season during spring and summer, which favors high water availability to the soil due to rainfall and less probability of occurrence of consecutive dry days. The authors also affirm that in order to obtain a good income from the agricultural activity, it is important to know the conditions of the environment and the culture, from before planting until postharvest, as the rainfall and the temperature of the air, together with the photoperiod, are the main meteorological variables for productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The reference ET data on Zenodo was previously published [ 33 ]. Dias et al, 2021 [ 33 ] calculated reference Et using a modified Penman-Monteith method [ [34] , [35] , [36] ] and weather data from INMET. Gray mold is the number one pest of castor production worldwide.…”
Section: Methodsmentioning
confidence: 99%
“…The knowledge of forecasting the probability of rainfall favors better agricultural planning and aids in the farmer's decision-making, which in turn reduces the risks in crop productivity (Garcia et al, 2013;Defiesta & Rapera, 2014;Barreto et al, 2015;Nyadzi et al, 2019), particularly in arid and semi-arid areas where water scarcity affects livelihoods and food security, as most of the available water comes from rainfall during the rainy season or groundwater close to the earth's surface (Abdalla et al, 2017). In this context, the objective was to analyze the probability of occurrence of monthly and annual rainfall, applying the probabilistic model Gama for the municipality of Chimoio, Mozambique.…”
Section: Introductionmentioning
confidence: 99%